Factors affecting university students intentions to use debit card services: an empirical study based on UTAUT - Kissi, Philip; Oluwatobiloba, Mustapha; Berko, Amankwah (Business, Management and Economics Engineering, 2017)
Despite the promising use of debit cards for e‐payment and online transactions, to the best of our knowledge, there has not been any study regarding students’ intentions to use debit card services in Nigeria. This research aims to examine factors that influence university students’ decision to use debit card services in Nigeria. A Unified Theory of Acceptance and Use of Technology (UTAUT) integrated with the trust of bank and online transaction factors are used in the study. Data were purposively selected from 400 students in the Faculty of Business Administration in Nigeria University using a survey questionnaire. The multiple linear regression results reveal that social influence, the trust of online transaction and performance expectancy exert significant influences on students’ behavioural intention to use a debit card. However, the insignificant results obtained for effort expectation and facilitating condition warrant for further investigation. We have confidence that the findings of this study will guide debit card services providers and professionals in the field in improving and promoting debit card services by revealing the students’ priorities regarding debit card services in Africa, particularly in Nigeria.